Pengaruh Bahan Tambah Superplasticizer pada Beton Porous Terhadap Kuat Tekan, Tarik Belah dan Permeabilitas - Danil Andriansyah; Eko Walujodjati (Jurnal Konstruksi, 2023)
Porous concrete is an innovation in sustainable concrete technology without fine aggregate with high porosity. This porous concrete can be used on road pavement to overcome water run-off, and can also be applied as a retaining wall which functions to minimize ground water pressure. This research intends to examine experimentally the mechanical properties of compressive strength, tensile strength and permeability of porous concrete with various variations in cement water factors. The coarse aggregate used for Cilopang crushed stone is sized 19 mm, 12.5 mm, 9.5 mm and uses added supperlasticizer. The sample used for testing compressive strength and split tensile strength was in the form of a cylinder measuring 15 x 30 cm. Based on the test results according to ACI 522R-10, the test results for porous concrete show that normal porous concrete using supperplasticizer additives has experienced changes in the value of compressive strength and splitting tensile strength compared to normal concrete.